Inflammation‐ and tumor‐induced anorexia and weight loss require MyD88 in hematopoietic/myeloid cells but not in brain endothelial or neural cells. Issue 5 (8th February 2013) - Ruud, Johan; Wilhelms, Daniel Björk; Nilsson, Anna; Eskilsson, Anna; Tang, Yan‐Juan; Ströhle, Peter; Caesar, Robert; Schwaninger, Markus; Wunderlich, Thomas; Bäckhed, Fredrik; Engblom, David; Blomqvist, Anders
Abstract : Loss of appetite is a hallmark of inflammatory diseases. The underlying mechanisms remain undefined, but it is known that myeloid differentiation primary response gene 88 (MyD88), an adaptor protein critical for Toll‐like and IL‐1 receptor family signaling, is involved. Here we addressed the question of determining in which cells the MyD88 signaling that results in anorexia development occurs by using chimeric mice and animals with cell‐specific deletions. We found that MyD88‐knockout mice, which are resistant to bacterial lipopolysaccharide (LPS)‐induced anorexia, displayed anorexia when transplanted with wild‐type bone marrow cells. Furthermore, mice with a targeted deletion of MyD88 in hematopoietic or myeloid cells were largely protected against LPS‐induced anorexia and displayed attenuated weight loss, whereas mice with MyD88 deletion in hepatocytes or in neural cells or the cerebrovascular endothelium developed anorexia and weight loss of similar magnitude as wild‐type mice. Furthermore, in a model for cancer‐induced anorexia‐cachexia, deletion of MyD88 in hematopoietic cells attenuated the anorexia and protected against body weight loss. These findings demonstrate that MyD88‐dependent signaling within the brain is not required for eliciting inflammation‐induced anorexia. Instead, we identify MyD88 signaling in hematopoietic/myeloid cells as a critical component for acute inflammatory‐driven anorexia, as well as for chronic anorexia and weight loss associated with malignant disease.—Ruud, J., Wilhelms, D. B., Nilsson, A., Eskilsson, A., Tang, Y.‐J., Ströhle, P., Caesar, R., Schwaninger, M., Wunderlich, T., Bäckhed, F., Engblom, D., Blomqvist, A. Inflammation‐ and tumor‐induced anorexia and weight loss require MyD88 in hematopoietic/myeloid cells but not in brain endothelial or neural cells. FASEB J. 27, 1973–1980 (2013). www.fasebj.org